M Mengenal Depresi dan Penanganannya Pada Wanita Usia Dewasa Sebagai Upaya Pencegahan Kekerasan Anak Dalam Rumah Tangga : Recognizing Depression and Its Handling in Adult Women as an Effort to Prevent Child Abuse in the Household - Wulansari Wulansari; Mukhamad Mustain; Fiktina Vifri Ismiriyam (Cv. Utility Project Solution, 2023)
Introducing depression and introducing depression treatment to adult women or housewives is one of the steps that can be taken as an effort to prevent violence against children. Violence against children can be carried out by people who are supposed to protect them, namely one of them is the mother. The mother here is in the group of adult women. Mothers who abuse their children do so because they experience psychological pressure. Violence against children can be prevented if people around them also know about depression and are able to provide assistance in handling it. The purpose of this community service activity is to increase the knowledge of groups of adult women and/or housewives about depression and its treatment so that there is no violence in children due to depressed mothers. Depression is a mental health problem that often arises and requires early detection for treatment so that it does not cause other problems such as violence against other people, especially children who should be protected. The method used is the implementation of health education interventions through health counseling and training on how to deal with depression in adult women. The result of this service activity is an increase in knowledge about depression to be good 59% and quite good 41% as well as the ability to recognize one's own condition and be able to treat depression and provide help to other women who are experiencing depression. So that in the future there will be no more violence against children by people who are supposed to protect and fellow women help other women.